A Preclinical Model for Colitis and Colitis-Associated Cancer - A Prerequisite for Drug Development - Jackson, Nicholas. (2018)
Abstract: Ulcerative colitis (UC) is an inflammatory bowel disease (IBD) that is located in the large intestine. Patients with UC have a shorter life expectancy, and an increased incidence of developing colorectal cancer (CRC). CRC contributes to the high mortality rates of cancer related death. Along with the increased risk of developing CRC, UC patients are also at a 20% increased risk of developing colitis-associate cancer (CAC). While CRC has been well studied, CAC progression has not been well characterized, warranting new studies to better understand this disease. The Wnt signaling pathway has been identified as a key factor in development of CRC. The transcriptional repressor gene, HBP1, has been identified to downregulate Wnt signaling. In this study we use a HBP1 knockout mouse model to investigate HBP1's role in UC and CAC. In vivo and in vitro studies suggest that the transcriptional repressor, HBP1, plays a role in the susceptibility and development of UC and colitis-associated colorectal cancer CAC. Currently, there are no biomarkers to predict UC or CAC. These studies suggest that HBP1 could be used as a possible biomarker for UC and CAC, while also offering a potential animal model to study UC and CAC. There is also a gap in knowledge understanding the UC to CAC progression, in which this animal model could provide more insight on the molecular mechanisms of UC to CAC progression. Lastly, these studies suggest that a pharmacological compound that suppresses Wnt signaling could potentially be used to reduce the effects of UC and CAC and their development.; Thesis (M.S.)--Tufts University, 2018.; Submitted to the Dept. of Pharmacology and Drug Development.; Advisor: Amy Yee.; Keywords: Pharmacology, and Translation studies.